2015
DOI: 10.1007/978-3-319-02696-1_2
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Prediction of Self-produced Energy

Abstract: The need for energy has been aggressively increasing since the industrial revolution. An exponential growth of industrial and residential power use is encountered with the technological revolution. Cogenerated and self produced energy is a solution that allows the reuse of heat produced, decreases transmission investments, and reduces carbon emissions and decreases dependency on energy resource owners. The mass production sites, health centers, big residential sites and more can use the system. In this chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…ANNs are intelligent systems that work by mimicking the biological nervous system and are inspired by the electrochemical information processing technique of the human brain. An ANN model is comprised of neurons that use inputs across the network and transform inputs using transfer functions to produce results [52]. In this study, a Multi-Layer Feed-Forward Backpropagation ANN structure, as demonstrated in Figure 4, is utilized for the estimation of wind speed.…”
Section: Ann-based Hybrid Models For Wind Speed Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…ANNs are intelligent systems that work by mimicking the biological nervous system and are inspired by the electrochemical information processing technique of the human brain. An ANN model is comprised of neurons that use inputs across the network and transform inputs using transfer functions to produce results [52]. In this study, a Multi-Layer Feed-Forward Backpropagation ANN structure, as demonstrated in Figure 4, is utilized for the estimation of wind speed.…”
Section: Ann-based Hybrid Models For Wind Speed Estimationmentioning
confidence: 99%
“…The inputs of each neuron are processed by a transfer function, from which the linked neuron's output is produced. The sigmoid and hyperbolic tangent functions are the most frequently used activation functions [52]. The hyperbolic tangent sigmoid (tansig) is preferred as the transfer function in that configuration because the relation between input and output neurons is nonlinear.…”
Section: Ann-based Hybrid Models For Wind Speed Estimationmentioning
confidence: 99%